Aberrant STING activation promotes macrophage senescence by suppressing autophagy in vascular aging from diabetes - Huiqing Ding; Quan Zhang; Rukai Yang; Liyao Fu; Hejun Jiang; Qingyi Zhu; Shi Tai (iScience)
Summary: Diabetic vascular aging is driven by macrophage senescence, which propagates senescence-associated secretory phenotypes (SASP), exacerbating vascular dysfunction. This study utilized a type 2 diabetes mellitus (T2DM) mouse model induced by streptozotocin injection and a high-fat diet to investigate the role of STING in macrophage senescence. Vascular aging markers and senescent macrophages were assessed in vivo, while in vitro, high glucose treatment induced macrophage senescence, enhancing senescence in co-cultured vascular smooth muscle cells. Mechanistic studies revealed that STING activation inhibits autophagy by phosphorylating ULK1 at S757, accelerating senescence. Pharmacological modulation showed that the STING inhibitor H-151 alleviates, while the agonist DMXAA enhances, senescence. These findings highlight the STING-autophagy axis as a critical driver of macrophage senescence, offering insights into the molecular mechanisms of diabetic vascular aging and identifying potential therapeutic targets to mitigate vascular complications in diabetes.